Soccer Clubs and Regional Image - Rüdiger Hamm (European Regional Science Association (ERSA), 2015)
A number of studies have been conducted trying to describe and estimate the regional economic effects of sports clubs, especially of soccer clubs. Most of these studies focus on demand-side effects because regional multiplier analysis seems to offer a powerful tool for this kind of estimations. In most cases these analyses come to the conclusion that there are significant demand-side effects. But firstly the results of calculating the demand side effects of soccer clubs by regional multiplier analyses should be handled with care because many assumptions are necessary offering analysts a wide range of possibilities to influence the results. And secondly the demand side effects of sports clubs do not exceed the demand side effects of a ?normal? medium-sized enterprise to a considerable extend; only the fans? expenditures might explain a positive difference. Nevertheless it seems that there is something more beyond regional multiplier analysis (CROMPTON), some additional regional effects of soccer clubs that bring benefit to the location of such a club. These effects stem from the supply side, they are especially connected with regional awareness and image and they are usually omitted from the analysis because quantification is nearly impossible. It is hardly possible, too, to quantify the effects of regional awareness and image for regional economic development. But analyses based on firm surveys suggest that regional image can be seen as an important location condition. That is why location theory often regards regional image as a separate ?soft factor of location?, that codetermines entrepreneurial decisions. Sports clubs and sports events are part of numerous factors that, in turn, influence regional image. This would mean that a soccer club that is able to transfer its (positive) image to its hometown might finally be able to affect regional economic development of this city positively. Aim of the following paper is to thoroughly analyse these relationships. Using VfL 1900 Borussia Mönchengladbach ? a well-known member of the German premier soccer league ? as an example the paper deals with the following questions: (a) Is it possible to identify awareness increasing effects of the soccer club for the city of Mönchengladbach, (b) which role can Borussia play as an important icon of the city of Mönchengladbach and (c) are there any hints that the club?s image can be transferred to the city? Part 1 of the paper systemizes and describes regional economic effects of a premier league soccer club. Using survey data the subsequent empirical considerations (part 2) try to qualify and (to a certain extend) quantify the mentioned effects by means of descriptive statistics as well as factor and regression analysis. The paper ends with some final remarks on the major findings (part 3).
Keywords: 330; Regional Image; Regional Development; Soccer